Early‐life sensitization to hen's egg predicts asthma and rhinoconjunctivitis at 14 years of age. Issue 8 (21st December 2017) - Christiansen, Elisabeth Soegaard; Kjaer, Henrik Fomsgaard; Eller, Esben; Bindslev‐Jensen, Carsten; Høst, Arne; Mortz, Charlotte Gotthard; Halken, Susanne
Abstract: Background: Sensitization to both inhalant and food allergens has been shown to be risk factors for development of asthma and rhinoconjunctivitis (RC). However, few studies have addressed the role of transient or persistent IgE sensitization to specific allergens in early life for later development of allergic diseases. The aim of this study was to explore the association between transient and persistent sensitization in early life and the development of asthma and RC at 6 and 14 years. Methods: The Danish Allergy Research Center (DARC) cohort is a prospective non‐interventional birth cohort study comprising 562 children. For the purpose of this study, we examined a subgroup of the original cohort with specific IgE measured at, at least 3 of 4 follow‐ups between 3 and 18 months of age (n = 366). Multiple logistic regression models were used to investigate the association between transient and persistent early‐life sensitization to groups of and to individual allergens and asthma and RC at 6 and 14 years compared to a reference group with no sensitization. Results: Both transient early‐life sensitization and persistent early‐life sensitization to cow's milk or hen's egg proteins were associated with asthma (aOR 3.99[1.41‐11.32] and 5.95[1.78‐19.92]) and RC (aOR 2.94[1.19‐7.28] and 6.18[1.86‐20.53]) at 14 years, this association being driven mainly by sensitization to hen's egg. Transient early‐life sensitization to house dust mite (HDM) had increased risk of asthma (aOR 3.80[1.17‐12.41]) at 14 years. Conclusions: Early transient IgE sensitization and persistent IgE sensitization to hen's egg were associated with asthma and RC at 14 years. Furthermore, sensitization to HDM was associated with asthma at 14 years.